Characteristics of Notary Deeds for Transactions Through Electronic Media - Kumara Putra, Fani Martiawan (NORMA, 2020)
These technological advances have caused enormous changes to business people who will indirectly use modern technological advances. This development will undoubtedly bring changes to the Notary duties and authorities' implementation as public official authorized to do authentic deeds. A new dynamic of society changes due to globalization and developments in information technology that require Notary services in carrying out existing legal actions, facilitated by current information technology. However, Notaries are still hampered by the absence of legal instruments that protect and regulate Notaries in carrying out these actions. This is a challenge for the Notary profession in responding to globalization in information technology, meaning that the Notary's duties as public officials develop along with the times. This research is normative research with a statutory approach. The results obtained from this research are that the Notary Public must involve a third party called the Certification Authority, to secure and legitimize documents into electronic transactions. The Notary deed to be used remains an authentic deed and has perfect evidentiary power. Still, suppose the process does not involve the party. In that case, the Notary deed is classified as an underhand deed, and has the power of proof as to the deed underhand, even though it is made and signed either directly or digitally by the Notary.Keywords: Notary, Electronic Transaction, Notary Deeds